Optimization of sensitometric properties of blue and green light sensitive dental radiographic films employing an automatic processor - Suchetha N Malleshi; Karthikeya Patil; Mahima V Guledgud (Wolters Kluwer Medknow Publications, 2011)
Background: Accurate film processing is of paramount importance in acquiring a good diagnostic radiograph. Radiographic films show variations in densities and contrast, with changes in processing conditions, and also film type, all of which are interdependent. Therefore, this research was conducted to recognize the effect of time and temperature variations of automatic processor on the sensitometric properties of blue and green light sensitive screen films. The study also aimed to note the effect on sensitometric properties when mismatch occurred when using between the screen and film belonging to different manufacturers. Materials and Methods: Sixty green light sensitive and 60 blue light sensitive spectrally matched screen film combinations were used in the study. However, the films and the intensifying screens employed belonged to different manufacturers. These films were exposed to five different exposure times and subsequently processed in an automatic processor, using two different protocols. Initially, at constant processing time of 2.5 min, five different processing temperatures were employed. Later, maintaining constant processing temperature of 35°C and five different processing times were engaged. Density, contrast and speed were calculated, using H and D curve. Results: Results revealed increasing density, contrast and speed values with increasing processing times and temperatures of both green and blue sensitive films. Conclusion: This investigation clearly establishes the possibility of obtaining optimal sensitometric properties, despite using intensifying screens and films of different manufacturers, if spectral match is ensured.